Engineering of Metabolic Pathways by Artificial Enzyme Channels - Pröschel, Marlene; Detsch, Rainer; Boccaccini, Aldo R.; Sonnewald, Uwe (Frontiers in Bioengineering and Biotechnology, 2015)
Application of industrial enzymes for production of valuable chemical compounds has greatly benefited from recent developments in Systems and Synthetic Biology. Both, in vivo and in vitro systems have been established, allowing conversion of simple into complex compounds. Metabolic engineering in living cells needs to be balanced which is achieved by controlling gene expression levels, translation, scaffolding, compartmentation and flux control. In vitro applications are often hampered by limited protein stability/half-life and insufficient rates of substrate conversion. To improve stability and catalytic activity, proteins are post-translationally modified and arranged in artificial metabolic channels. Within the review article we will first discuss the supramolecular organization of enzymes in living systems and secondly summarize current and future approaches to design artificial metabolic channels by additive manufacturing for the efficient production of desired products.